Biological and synthetic scaffold: an extra cellular matrix for constructive tissue engineering - Kannaiyan, Jaianand; Chhabra, Hemlata; Palaniyandi, M; Rajangam, B; Narayanan S, Suriya; Pandey, Anubhav (International Journal of Medical Research and Review, 2016)
Worldwide many people suffering from tissue dysfunctions or damages need rapid transplantation. Tissue engineering has attracted attention as therapeutic modality aiming at repairing lost or damaged tissues. Critical step in tissue engineering is fabrication of three dimensional scaffolds which mimic the extracellular matrix of tissues and promote tissue regeneration process. Extensive research has been carried out to develop a compatible scaffold which mimic the anatomical site of injury and as well as accessing the stem cells and growth factors to home on the injured site. The present article provides an overview on different scaffold approaches and materials used to fabricate scaffolds, with their properties and associated advantages and disadvantages. In particular, the therapeutic potential of amniotic membrane and collagen scaffold has been extensively reviewed in here.